PTU-082 Responders to haemopoietic stem cell transplantation for crohn's disease. (22nd June 2015) - Hawkey, C; Allez, M; Clark, M; Labopin, M; Lindsay, J; Ricart, E; Rogler, G; Satsangi, J; Kaye, P; Sharratt, C; Farge, D
Abstract : Introduction: We recently reported that about one third of patients with Crohn's disease experience prolonged regression of ileocolonic disease following haemopoietic stem cell transplantation (HSCT). Here we compare the characteristics of responders and non-responders. Method: Patients with impaired quality-of-life from active Crohn's disease not amenable to surgery despite treatment with at least 3 immunosuppressive agents all underwent stem cell mobilisation before randomisation to immuno-ablation followed by unselected cyclophosphamide-based conditioning and HSCT after one month (Early HRCT) or one-year (Delayed HS CT). Patients in whom all endoscopic evidence of Crohn's disease disappeared (SES-CD score of zero) were classified as Responders. Supporting histology was available in 17 of them. Results: Forty four patients with ileocolonic involvement underwent mobilisation before randomisation to Early or Delayed HSCT. Of 38 patients that could be classified 14 were Responders. Ten had SES-CD of zero after 1 year, (maintained in the second in 3 of 4 with available data) and 4 achieved responder status in year 2. Four of 6 followed to 4 years remain free of Crohn's disease vs 1 of 15 non-responders. Responders were significantly more likely to have histologically normal segments post HSCT (Table 1 ) A Responder status tended to be more likely with no family history (39% vs 20%), in non-smokers (54% vs 30%), with early-onset of disease (Montreal A1, 46% vs 32%)) and with more than 10 year history (46% vs 17%); those with pure colonic involvement (L2) were less likely to respond than those with ileal involvement (L1, L3, 14% vs 43%) but these fell short of statistical significance on univariate analysis. Conclusion: A group of patients can be identified who have a substantial and long lasting regression of Crohn's disease following HSCT. Endoscopic response following HSCT is associated with regression of histological evidence of Crohn's disease. Disclosure of interest: None Declared.